A COGNITIVELY ORIENTED DIAGNOSTIC ASSESSMENT OF NUMERACY LITERACY: DEVELOPMENT AND EXPERT VALIDATION - Rizky Fadillah; Rachmat Wasqita (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
Numeracy literacy achievement among Indonesian students remains critically low, yet contextually situated diagnostic instruments are largely unavailable. This study develops a cognitively oriented diagnostic assessment instrument in mathematics, grounded in Sumbawa's local numeracy literacy context, for Phase D students across Grades VII, VIII, and IX. Development followed Thiagarajan's 4D framework: Define, Design, and Develop, involving observation, interviews, and curriculum analysis. The Design phase produced five integrated components test blueprints, item sets, answer keys, scoring rubrics, and interpretive guidelines differentiated across Bloom's cognitive levels (C1–C6) and anchored in local culture. Prototype I was validated by nine experts: three lecturers and two practitioner teachers per grade level, covering content, construct, and language aspects. Quantitative scores were analyzed using Aiken's V; qualitative feedback through thematic analysis. Three aspects achieved highly valid ratings across all grades (mean: 95.09%), with Aiken's V exceeding 0.80 for all items. Validators affirmed alignment with diagnostic purposes, numeracy indicators, and local context, guiding revisions producing Prototype II. Findings show that integrating Bloom's Taxonomy, numeracy literacy, and local culture within a diagnostic framework is theoretically coherent and feasible. The absence of student trials and psychometric analyses are acknowledged, with future directions proposed.